Solar photocatalysis applied for water detoxification and decontamination - Fernández Ibáñez, Pilar (2010)
One characteristic that best defines today's society is the production of waste, this being higher in so-called "developed" countries. Virtually no human activity that does not generate any waste also exist a direct relationship between the standard of living of a society or country and the amount of waste generated. Approximately 23% of the world population lives in developed countries consume 78% of resources and produces 82% of the waste [Black and Malate, 1996]. Furthermore, the volume of waste grows exponentially with the level of industrialization of a country. There are currently about five million registered substances known of which approximately 70,000 are widely used throughout the world, estimated at about 1,000 new chemicals each year are added to the list.